2011
DOI: 10.1364/ao.50.004268
|View full text |Cite
|
Sign up to set email alerts
|

Development of a variable launch attenuation and isolation measurement system for optical waveguides

Abstract: In this paper we describe a system that measures the attenuation and isolation of optical waveguides and has the capability to fully explore these properties over a range of reproducible launch conditions. The system allows both the launch signal spot size and numerical aperture to be varied and can be correlated to the actual operating conditions of the board. Characterization of the optical system, including the magnification factor as well as the linearity, sensitivity, spatial uniformity of the charge-coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Another potential metrological platform is the use of a variable launch system, such as that used at NPL and shown in figure 5 [11,12], that can control the launch of a laser, in terms of spot size and numerical aperture, into a particular waveguide to assess attenuation, encircled flux and bit error ratio. This system provides flexibility to assess individual fibres or waveguides embedded onto interconnect boards as well as silicon-based PIC's/QPIC's and provides information on coupling efficiencies and functional performances under different operating conditions [13] 2 QPIC's Photonic Integrated Circuits (PICs) have seen extensive development over the past decade and are important components for the future of optical communications and optical metrology (eg: LIDAR and fibre-optic sensing applications).…”
Section: Figure 1:e-2000 Connector Image Courtesy Ofmentioning
confidence: 99%
“…Another potential metrological platform is the use of a variable launch system, such as that used at NPL and shown in figure 5 [11,12], that can control the launch of a laser, in terms of spot size and numerical aperture, into a particular waveguide to assess attenuation, encircled flux and bit error ratio. This system provides flexibility to assess individual fibres or waveguides embedded onto interconnect boards as well as silicon-based PIC's/QPIC's and provides information on coupling efficiencies and functional performances under different operating conditions [13] 2 QPIC's Photonic Integrated Circuits (PICs) have seen extensive development over the past decade and are important components for the future of optical communications and optical metrology (eg: LIDAR and fibre-optic sensing applications).…”
Section: Figure 1:e-2000 Connector Image Courtesy Ofmentioning
confidence: 99%
“…The modified variable launch system is shown in Figure 1 and builds on previous work carried out at NPL (Ives, 2011, Ferguson, 2007. Light from an 850 nm VCSEL laser is launched into a step-index fibre with a 365 µm core and a numerical aperture (NA) of 0.22.…”
Section: The Modified Measurement Systemmentioning
confidence: 99%
“…The current issue and full text archive of this journal is available at www.emeraldinsight.com/0305-6120.htm Circuit World 36/2 (2010) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] q Emerald Group Publishing Limited [ISSN 0305-6120] [DOI 10.1108/03056121011041654] The partners in the project, whose research is reported, gratefully acknowledge financial support from the UK EPSRC via the IeMRC. The three universities gratefully acknowledge the financial support provided by the eight companies in direct and indirect contributions which was significantly higher than originally envisaged.…”
Section: Motivation For the Researchmentioning
confidence: 99%
“…Multiple measurements of waveguides on the same and different wafers enabled the uniformity and measurement reproducibility to be established. During the project, NPL developed an imaging measurement technique (Ives et al , 2009; Ives, 2008a, b), which was found to give results in good agreement with UCL to within the experimental measurement accuracies. UCL and Xyratex also jointly carried out bit error rate and eye diagram measurements on the advanced fully connected backplane waveguide design (Wang et al , 2008b; Pitwon et al , 2010) (Figure 15).…”
Section: Waveguide Quality Test and Measurementmentioning
confidence: 99%